Hubungan Dukungan Sosial Secara Daring Melalui Twitter Dengan Perilaku Nonsuicidal Self-Injury Pada Remaja - Luluk Puji Rahayu, Anggun; Dian Ariana , Atika (CV RIFAINSTITUT, 2023)
This study aims to determine the relationship between online social support on Twitter and nonsuicidal self-injury behavior in adolescents. Online social support is a new form of social support that is developing among social media users. Nonsuicidal self-injury behavior is self-injury behavior without suicidal intent. The participants of this study were 191 adolescents Twitter users on Twitter who had hurt themselves without suicidal intentions. Data were collected using the Online Social Support and the Inventory of Statements about Self-Injury. Data were analyzed using Spearman's rho correlation technique on Jamovi 1.6.15 for Windows. The results of the analysis indicate that there was no significant relationship between online social support on Twitter and non-suicidal self-injury behavior in adolescents (p=0.284; r=-0.042). It is important to explore further between nonsuicidal self-injury behavior and other internet-related variables.